Factors Related to the Incidence of Primary Dysmenorrhea in STIKes Muhammadiyah Cirebon Students in 2023 - Tritanti, Lulu; Mutya Sari, Vianty; Rizki Nurfita, Nisa; Nurul Hidayah, Fika (Jurnal Medisci, 2024)
The rate of dysmenorrhea is 50% experienced by all ladies within the world. Dysmenorrhea is a torment that happens amid a monthly cycle. The effect of essential dysmenorrhea can lead to fruitlessness or fruitlessness. Variables that can impact the event of dysmenorrhea are age at menarche, length of monthly cycle, body mass record, family history, and need to work out. This investigation, conducted utilizing observational analytics with a cross-sectional plan, points to recognizing the variables related to essential dysmenorrhea. The investigated test, comprising 40 respondents, was chosen through arbitrary inspection. The inquiry about the instrument utilized was a survey. Univariate information was analyzed distinctly, and bivariate information was analyzed utilizing the Chi-Square Test. The dissemination of essential dysmenorrhea in female STIKes Muhammadiyah Cirebon understudies was 32 respondents (80.0%). The most elevated extent of respondents who experienced essential dysmenorrhea was at the age of menarche, and there were 22 respondents (67.5%) with the comes about of the Chi-Square test p=0.037. The more significant part of the normal menstrual term was 32 respondents (80%) with the Chi-Square test, which comes to about p=0.004; the body mass file included within the ordinary category were 23 respondents (57.5%) with the Chi-Square test comes to about p=0.013. A family history of 25 respondents (62.5%) with Chi-Square test comes about p=0.002. There are 29 respondents (72.5%) who work out.